PERBANDINGAN HASIL BELAJAR ANTARA KOOPERATIF LEARNING TIPE TIPE THINK PAIR DAN PEMBELAJARAN PROBLEM BASED INSTRUCTION - Duwi Wahyuni; I Dewa Putu Nyeneng; Undang Rosidin (Jurnal Pembelajaran Fisika, 2012)
Using Problem Based Instruction method is capable to improve Learning outcomes compare to Cooperative Learning method, particularly Think Pair Share type. Outcomes is measured based on final exam result.The intent of this comparison study using two above methods is allowing us to differentiate the average cognitive aspect of student’s learning outcomes in physics. The design of this study uses Post Test-Only Control type in Quasi Experiment Design form. The analytical of learning outcome uses the mean score of final exam, while the hypothetical uses independent Sample T-Test,Refers to independent test result analysis between Problem Based Instruction and Think Pair Share method, there is difference in average mark two clases gained in their final exam. Quantitative data shows that Problem Based Instruction method has higher value compare to Think Pair Share method. Students in the class who are using Problem Based Instruction methode have become proactive and directly involve in learning process. It may lead us to effectivemess of the method that has significant contribution in improving student's learning outcom.Keywords: Problem Based Instruction, Cooperative Learning Think Pair Share Type, Learning Outcomes.